Analisis Hukum Positif Dan Syariah Di Indonesia Pada Kontrak Bisnis Dan Jual Beli Perdagangan - Faizza Al-Fathi Muslimah; Romi Faslah (CV. ITTC INDONESIA, 2025)
This article discusses business contracts and buying and selling in the perspective of positive law and sharia law in Indonesia. The main issues raised include differences in philosophy, legality, dispute resolution, and the role of Islamic financial institutions and DSN-MUI fatwas in business practices. The purpose of the study is to analyze the similarities and differences in the concepts and legal implications of the two systems. The approach used is a normative study with a qualitative descriptive method based on legal literature analysis and case studies. The results show that contracts in positive law emphasize freedom of contract and legal certainty, while sharia law focuses on substantial justice, prohibition of usury, and ethics of muamalah. The integration of the two reflects Indonesia's unique legal pluralism and can create a fair and balanced trading system.